Natural Environment Character Education Based on Islam - Muhammad Yusuf; Mardan Mardan; Nahdiyah Nahdiyah (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2019)
Character education oriented toward the environmental care is required in the local, national and global scales following the environmental crisis and the unbalance of the ecosystem that harms mankind. Education is the most effective means for dealing the aforementioned challenges. Drawing on the concept of the Quran and Sunnahthematically, the complete concept regarding the character education oriented toward the environmental care was uncovered, namely the education of environmental awareness based transcendental values because its correspondence to the nature of mankind. The highest value of character education is based on the spirituality that views the nature as tajjalli(the self-manifestation of God) and signal of god. The principles of character education should be well-planned, gradual, controllable, evaluative and sustainable. In such a context, understanding, habituation, exemplary models, culture, consistent regulation are required, which are subsequently internalized and at the end become a character.